2015
DOI: 10.1002/hep.27344
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in melanoma differentiation‐associated gene 5 link protein function to clearance of hepatitis C virus

Abstract: Among patients newly infected with hepatitis C virus (HCV), only 20–30 % clear the infection spontaneously. In the remaining 70 %, the infection persists causing chronic liver inflammation and disease. It is well established that polymorphisms in host genes, especially in components of the innate immune response, contribute to the phenomenon of spontaneous HCV clearance. RIG-I-like helicases such as MDA-5 are cytoplasmic sensors of viral RNA that are critical for triggering innate immune responses after infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 44 publications
6
41
0
Order By: Relevance
“…1A). A more significant association with SC was obtained with the C allele of rs1990760 (A946; OR for C/C vs. T/C 5 1.69; 95% CI: 1.18-2.44; P one-sided 5 0.005), consistent with the trend shown in Table 2 of Hoffman et al (1) Multivariate analysis confirmed that the effect of rs1990760 was independent of the IL28B SNP rs12979860. Linkage disequilibrium (LD) analysis on our cohort revealed that rs3747517 and rs1990760 were in strong LD (D'=1; r 2 5 0.33).…”
Section: To the Editorsupporting
confidence: 84%
See 3 more Smart Citations
“…1A). A more significant association with SC was obtained with the C allele of rs1990760 (A946; OR for C/C vs. T/C 5 1.69; 95% CI: 1.18-2.44; P one-sided 5 0.005), consistent with the trend shown in Table 2 of Hoffman et al (1) Multivariate analysis confirmed that the effect of rs1990760 was independent of the IL28B SNP rs12979860. Linkage disequilibrium (LD) analysis on our cohort revealed that rs3747517 and rs1990760 were in strong LD (D'=1; r 2 5 0.33).…”
Section: To the Editorsupporting
confidence: 84%
“…Linkage disequilibrium (LD) analysis on our cohort revealed that rs3747517 and rs1990760 were in strong LD (D'=1; r 2 5 0.33). Thus, the rare H843/T946 haplotype identified as the strongest predictor of SC (1) was not observed in this Egyptian population. Our haplotype analysis for rs3747517-rs1990760 showed that SC was the most strongly associated with haplotypes carrying allele C (TC or CC) of rs1990760 (OR 5 1.69; 95% CI: 1.18-2.44; P 5 0.005; Fig.…”
Section: To the Editormentioning
confidence: 58%
See 2 more Smart Citations
“…Multiple Genome Wide Association (GWA) studies have shown that MDA5 is not only involved in antiviral immunity [31], but also in pathogenesis of several immune disorders, such as type 1 diabetes [32, 33], systemic lupus erythematosus [34, 35], multiple sclerosis [36] and rheumatoid arthritis [37]. Single nucleotide polymorphisms (SNPs) in the MDA5 gene ( IFIH1 ), such as T946A, R843H, E627X and I923V, were shown to be complete or partial loss-of-function mutations and to be associated with protection from these diseases [17, 31, 38, 39].…”
Section: Dysregulation and Immune Disordersmentioning
confidence: 99%